Prosthetic rehabilitation of a patient after partial maxillectomy: A clinical report - Shobha J Rodrigues; Sharon Saldanha (Wolters Kluwer Medknow Publications, 2011)
Malignant melanoma of the oral cavity is very rare. This clinical report describes a method for prosthetic rehabilitation of a patient with malignant melanoma of the palate following partial maxillectomy with a closed hollow interim obturator.